PENERAPAN PROSEDUR PENGAJUAN DAN PERTANGGUNGJAWABAN UANG MUKA DINAS KEGIATAN OPERASIONAL PADA PT PAL INDONESIA - Azhar Putri Nabila; Munari Munari (CV. Denasya Smart Publisher, 2025)
This study discusses the utilization of service progress operational activities at PT PAL Indonesia. The purpose of this study is to evaluate how well the current procedures are implemented and to identify any obstacles that arise during the process of submitting and accounting for service advances. A descriptive qualitative methodology was used, with data collected through observation, interviews, and documentation. The findings indicate that the procedures for submitting and reporting service advance payments have been carried out in a structured manner, supported by the digital IM4 system and a layered verification mechanism to minimize errors. However, challenges remain, such as delays in fund disbursement due to budget limitations, which impact the timely execution and reporting of activities. The use of digital technology has proven to enhance efficiency and transparency in managing operational finances. This research provides valuable insights for the development of a more effective and timely service advance management system, while also emphasizing the importance of budget strengthening and employee training to support smooth operations.